Diseño y evaluación mediante modelamiento de un sistema solar fotovoltaico comercial (2021)
As a first step for this project, a computational model was created. This model would allow us to simulate solar photovoltaic systems using the Pvlib-Python tool, having reliable and non-reliable values of radiation. Once the model was finished, its effectiveness was tested, comparing the simulated results of output energy with the measured results in the solar photovoltaic system of Universidad de los Andes. When the model was proven to be accurate, it was used for various configurations of solar photovoltaic systems at the Colegio Hebreo Union (Barranquilla, Colombia) in order to apply the model in real life. After using the energetic results and carrying out some financial analysis on each configuration, the best one was chosen. It was concluded that the model is quite accurate and an excellent initial tool to study solar photovoltaic projects...